GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 4446 species occurrences available in GBIF matching the query: TaxonKey: Abrus precatorius L.. The dataset includes 4446 records from 149 constituent datasets: 2 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 3 records from Guadeloupe_Herbier. 6 records from OEH Atlas of NSW Wildlife. 22 records from Phanerogamic Botanical Collections (S). 23 records from PRECIS (KwaZulu-Natal Herbarium). 17 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 10 records from Census of the flora of Benin. 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 3 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 3 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 402 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from SPSF - Herbário Dom Bento José Pickel. 5 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 67 records from PRECIS. 2 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 5 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 27 records from Census of plant species in Bonou forest reserve (Southern Benin). 1 records from UFP - Herbário UFP - Geraldo Mariz. 2 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from ICN - Herbário do Instituto de Ciências Naturais. 56 records from IICT Herbário LISC. 4 records from Herbario Universidad de Antioquia (HUA). 52 records from The digitization of plant specimens of NTU. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 22 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 3 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 2 records from CESJ - Herbário Leopoldo Krieger. 1 records from LISU Herbario Angola. 3 records from Herbier du Bénin. 1 records from MBM - Herbário do Museu Botânico Municipal. 4 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Inventaire floristique de Beza Mahafaly. 56 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Herbier de Nouvelle-Calédonie. 1 records from Herbarium of the Université Libre de Bruxelles. 10 records from tef-database. 531 records from Australia's Virtual Herbarium. 22 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 9 records from iNaturalist research-grade observations. 8 records from CONN. 2 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 15 records from ALCB - Herbário Alexandre Leal Costa. 114 records from NMNH occurrence DwC-A. 4 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 1 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 15 records from Census of plant species in Toffo forest reserve. 1 records from naturgucker. 14 records from Census in Agrimey forest reserve (southern Benin). 955 records from Flora Atlas N.T.. 56 records from INPN - Données flore des CBN agrégées par la FCBN. 2 records from Herbier de Wallis et Futuna. 1 records from EFC - Herbário Escola de Florestas Curitiba. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 13 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 2 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 1 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 180 records from Missouri Botanical Garden. 7 records from Natural History Museum (London) Collection Specimens. 1 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Formación del banco de datos del herbario (UCAM). 1 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 4 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 20 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 9 records from The AAU Herbarium Database. 18 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Jardín Botánico de Córdoba: Herbarium COA. 2 records from Botanic Garden of the Finnish Museum of Natural History. 1 records from herbario. 1 records from Database Schema for UC Davis [Herbarium Labels]. 1 records from Herbarium (UNA). 30 records from NSW herbarium collection. 19 records from Plants of Papua New Guinea. 12 records from Herbarium Berolinense. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 3 records from United States National Plant Germplasm System Collection. 28 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from Harvard University Herbaria. 14 records from EURISCO, The European Genetic Resources Search Catalogue. 2 records from CVRD - Herbário da Reserva Natural Vale. 2 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 4 records from MAR - Herbário do Maranhão. 17 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 4 records from Herbier Ecole de Faune. 24 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 5 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from MISS_DC_01MAR2006. 3 records from UA Herbarium. 8 records from Herbarium Senckenbergianum (FR). 4 records from SINGER Coordinator. 6 records from Database of Native Plants in Taiwan. 13 records from Herbier de la Guyane. 5 records from University of Ghana - Ghana Herbarium. 16 records from Herbarium of Taiwan Forestry Research Institute. 4 records from Herbario Amazónico Colombiano. 8 records from Precis Plant Data. 2 records from WII Herbarium Dataset. 5 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 10 records from tef-database. 4 records from HURB - Herbário do Recôncavo da Bahia. 5 records from TEPB - Herbário Graziela Barroso. 4 records from Herbarium togoense. 6 records from HST - Herbário Sérgio Tavares. 20 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 526 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 98 records from Bernice P. Bishop Museum. 3 records from FURB - Herbário Dr. Roberto Miguel Klein. 3 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 13 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 25 records from Seed collection – Dead seeds for evaluation and observation purposes. 6 records from Royal Botanic Garden Edinburgh Herbarium (E). 12 records from Botany (UPS). 23 records from Instituto de Ciencias Naturales. 31 records from Census of species recorded during phytosociological surveys in Benin. 12 records from JPB - Herbário Lauro Pires Xavier. 15 records from EAC - Herbário Prisco Bezerra. 30 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 20 records from R - Herbário do Museu Nacional. 39 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 34 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 1 records from Specimens from India at the Natural History Museum at the University of Oslo (NHM-UiO). 1 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 52 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 120 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from UB - Herbário da Universidade de Brasília. 2 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 2 records from Instituto de ciencias naturales. 2 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 26 records from Allan Herbarium (CHR). 19 records from SysTax - Botanical Gardens. 1 records from HPL - Herbário do Jardim Botânico Plantarum. 5 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 7 records from Vascular Plant Herbarium, Oslo (O). 7 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1 records from EAN - Herbário Jaime Coelho de Moraes. 34 records from Census of plant species in Pahou forest reserve. 1 records from Colección del Herbario del Jardín Botánico de la Universidad Nacional de Colombia Sede Caribe. 7 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 5 records from Geneva Herbarium – General Collection (G). 3 records from Instituto de Botánica Darwinion. 2 records from CPAP - Herbário CPAP. 7 records from MOSS - Herbário Dárdano de Andrade Lima. 3 records from HRCB - Herbário Rioclarense. 1 records from PACA-AGP - Herbarium Anchieta. 1 records from Millenium Seedbank (MSB).
Keywords: GBIF; biodiversity; species occurrences